O mundo é dos micróbios? Abordando a microbiologia no ensino médio por meio de atividades investigativas - Aline Constancio Ladeira (2021)
Biology teachers at the elementary school have increasingly sought to diversify the way they plan and execute their classes for to motivate and arouse the interest and enchantment of students with the content studied. This is especially necessary in the approach of some domains of knowledge, which may seem very abstract and distant from the students' daily lives, as in the field of Microbiology. In this regard, it is essential that new methodologies are developed so that the teaching / learning of regular high school students in this area takes place effectively, providing a reflection on their training as critical citizens and aware of their role as a member of society. The present work presents a didactic sequence based on activities of an investigative nature, for teaching the basic concepts of Microbiology to students in the second year of High School. The didactic sequence consisted of four main stages. Initially, a data collection was carried out on the perception that the research participants brought about the world of microorganisms through the application of a questionnaire. Then, investigative activities were carried out with the students, who carried out research on the presence of microorganisms in the school environment, through the inoculation of bacteria and fungi in Petri dishes containing commercial culture media and developed by the students themselves. In the third stage, students were encouraged to raise hypotheses and observations about the results obtained, through debate, by the production of concept maps and by the construction of a mural to communicate the main conclusions reached. Finally, the Post-questionnaire was applied at the end of all activities. During the comparison between the Pre and Post- questionnaires and the observation of the students 'involvement during the didactic sequence, it was clearly perceived, in a quanti-qualitative way, that there was consolidation of concepts and reduction of some of the students' knowledge gaps related to the Microbiology. It is concluded, through the analysis of the results obtained with the answers present in the questionnaires and with the qualitative observation of the involvement and commitment of the students during the accomplishment of the activities of the didactic sequence, that the investigative activities fulfilled their role of stimulating the construction and understanding of Microbiology concepts. This confirms the effectiveness of this methodology developed with the students. The product of this work was an e-book containing the innovative didactic sequence with investigative activities focused on the knowledge of microorganisms and their role in different environments.